The Making of Islamist-inspired Terrorism and It’s Counter-terrorism in Indonesia - Arrobi, Mohammad Zaki (Political Science Program, Universitas Negeri Semarang, 2018)
The study attempts to uncover the making of Islamist-inspired terrorism and its state-led counter-terrorism responses in the modern history of Indonesia. It argues that Islamist-inspired terrorism and its counter-terrorism have been inextricably linked in complex ways within political and historical contexts. Instead of regarding Islamist-inspired terrorism and counter-terrorism as separated and unrelated entities, or perceiving the latter as just response to the former, it suggests that they have been intertwined and shaped each other throughout Indonesiaâ€™s modern history. By discussing Islamist-inspired terrorism in the three Indonesian historical periods, namely the resurgence of Darul Islam during 1940-60s, the re-emergence of Darul Islam networks and its series of terrorist attacks in 1980s, and Â the Jemaah Islamiyah-related terrorist activities in the 2000s as illustrative cases, the study has delineated the ways in which Islamist-inspired terrorism and its state-led counter-terrorism have been bound up within particular political, historical, and sociological context. In addition to that, the study also reveals that both Islamist-inspired terrorism and its state-led counter-terrorism have been shaped by the dynamic interplay of local, national, and global contexts.